Kajian Daya Dukung Tanah Gambut dengan Perkuatan Geotekstil dan Perubahan Muka Air Tanah - Martini Martini (Jurusan Teknik Sipil Universitas Tadulako, 2018)
Peat soils have a high compressibily and low bearing capacity. This unfavourable characteristic might cause differential settlement dan failure of the construction, so that the appropriate improvement method is required to overcome this problem.Peat soil improvement method that commonly used is mechanically dan chemically soil improvement method. In this research, the peat soil reinforced with geotextile was conducted in order to find its influence in increasing the bearing capacity.Also, peat land are generally located in the area with shallow water level. In this research shallow foundation reinforced with geotextile with variations ground water level was conducted to determine its effect in improving the bearing capacity. The variation of layer number of reinforcement (N) used was N= 3, with width 2B reinforcement, where the variations of ground water level are z = 0 cm, z = 5 cm and z = 10 cm where B is foundation width and z are the distance of the ground water level from base of the foundation. Result of modeling in the laboratory shows that the insertion of geotextile material in the peat soil can increase its soil bearing capacity. The increasing of ultimate bearing capacity (qu) tends to be higher for reinforced soil with no ground water level compared to soil with ground water level.The closer ground water level to foundation base the smaller the bearing capacity either with or without reinforcement. The highest value of bearing capacity was obtained in reinforced peat soil with no water level that is 8,6 kN/m2 or the it increase as much of 178,1% compared to unreinforced peat soil with no water level. Bearing capacity ratio (BCR) has also increase as of as 2,78 in with the reinforcement without water level compared to condition without reinforcement and without water level.